Risks of Rural Communities in the Era of the Covid-19 Pandemic - Faraz Sumaya (Program Studi Sosiologi Fakultas Ilmu Sosial dan Ilmu Politik Universitas Maritim Raja Ali Haji, 2021)
Rural communities are among those affected by the Covid-19 pandemic that occurred globally This article attempts to analyze the impact that occurs using Risk Society Theory with literature study methods as a necessary data collection. From the results of the analysis, villagers fall into the criteria of at-risk communities, especially in the case of the Covid 19 pandemic which makes rural communities have a large impact and risks such as increasing unemployment, poverty, anxiety, and uncertainty due to this pandemic situation.